Usability Dalam User Experience Pada Penggunaan Sistem Informasi Rumah Sakit Gigi dan Mulut UMY - Sigit Yuniarto (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2018)
This research is to analyze the usability of the user’s experiences for informatics system in Rumah Sakit Gigi dan Mulut Universitas Muhammadiyah Yogyakarta (RSGM UMY) in university student and management staff perspectives. USE Questionnaire is one of the instruments which consist of questionnaires use to measure usability research. It is applied since the research consist three dimension of usability measurement, such as affectivity, efficiency and satisfaction from users. However, this research’ questionnaire consist of four aspects of usability; usefulness, ease of use, ease of learning and satisfaction. The analysis was done use the application of data analysis (excel) and SPSS as the statistical tool. The result exemplify whole of good usability in RSGM informatics system need to be able to support the user for carrying out the work in effective and efficient ways. Several weakness was found in the satisfaction aspect, especially in the menu of information system and supporting networks of the informatics systems.